Case Report: Ultrasound “whirlpool sign” in fetal intestinal malrotation and torsion: a case-based approach to early diagnosis and intervention - Liu, Yueyun; Zheng, Rongjie; Liu, Zonghua; Zhou, Jun (Frontiers in Pediatrics, 2025)
IntroductionFetal ascites is a rare condition that may indicate underlying gastrointestinal malformations, including congenital intestinal malrotation. Early recognition and timely intervention are crucial to prevent complications such as intestinal torsion and ischemic necrosis. This study reports a case of fetal intestinal malrotation presenting with isolated ascites and acute fetal distress, emphasizing the role of ultrasound and multidisciplinary management in improving neonatal outcomes.Case ReportA late-term fetus presented with reduced fetal movements. Ultrasound revealed moderate ascites, bowel dilation, and the characteristic “whirlpool sign,” suggesting intestinal malrotation with volvulus. Doppler ultrasound indicated abnormal umbilical artery blood flow, and cardiotocography (CTG) confirmed fetal distress. An emergency cesarean section was performed after a multidisciplinary consultation. Intraoperative findings revealed intestinal volvulus, and postoperative evaluation confirmed ischemic necrosis. The neonate underwent abdominal paracentesis and received comprehensive treatment, including respiratory support, antimicrobial therapy, and nutritional management. Histopathological examination confirmed localized intestinal necrosis without perforation. The infant recovered well and was discharged in stable condition.ConclusionFetal ascites may be an early sign of congenital intestinal malrotation and volvulus. The ultrasound “whirlpool sign” indicates intestinal malrotation and possible volvulus, aiding early detection but not confirming bowel necrosis. Prompt multidisciplinary decision-making is essential to improve perinatal outcomes and prevent severe complications.